Malaysiana collection at the University of Malaya library - Sinnasamy, Janaki (Persatuan Pustakawan Malaysia, 2011)
Malaysiana collection at the University of Malaya is defined as: (i) Books about Malaysia published locally or overseas, (ii) Books/Conference papers/Journal articles written by Malaysian and (iii) Books/Journals/Conference proceedings published in Malaysia regardless of the contents. The collection development adheres to materials which are scholarly and academic in nature. Whilst the acquiring of books is particularly in the areas of Malay language, literature and culture, journal articles and conference papers follow a much wider scope. The University of Malaya with collections published as early as the 17th Century has always been the prime spot for researchers dwelling in local content from both within the country and from overseas. This paper will discuss the Malaysiana information resources at the University of Malaya Library and its accessibility to the researchers.